Taganrog, Russische Föderation: Die Arbeiten des Jahres 2013 - Dally, Ortwin; Huy, Sabine; Larenok, Pavel A.; Schunke, Torsten (e-Forschungsberichte des DAI, 2023)
After the completion of the German-Russian excavations in the early Greek trading post of Taganrog at the mouth of the river Don (2004–2010) 14C-data have been commissioned again in 2013. The new data allow corrections of the stratigraphy by dating and reassessing the different levels and erosion phases.